mRNA-HPV Therapeutic Vaccine Encoding E6 and E7 Improves Therapeutic Potential in HPV-mediated Cancer - Lee, Seonghyun; Yoon, Hyunho; Hong, Seol Hee; Bang, Eun-Kyung; Kwon, Sung Pil; Kwak, Hye Won; Park, Hyo-Jung; Lee, Jisun; Park, Hyeong-Jun; Bae, Seo-Hyeon; Youn, Hyewon; Keum, Gyochang; et al. (JOURNAL OF IMMUNOLOGY, 2023)
The viral E6 and E7 oncoproteins of human papillomavirus (HPV) are strongly associated with cervical cancer. We developed and assessed the efficacy of an mRNA-HPV therapeutic vaccine (mHTV), containing the E6 and E7 proteins, in C57BL/J mice. mHTV generated robust T cell-mediated immune responses and induced short-lived effector and E7 tetramer-specific T cells. mHTV immunization significantly suppressed tumor growth in mice implanted with TC-1 tumor cells and improved overall survival. The re-transplantation of tumor cells into mice that survived the primary tumor challenge after primary vaccination led to the complete inhibition of tumor progression in all mHTV-treated mice. This showed that mHTV can effectively suppress cancer recurrence. mHTV also increased the number of tumor-infiltrating lymphocytes in the tumor tissues. When mice were implanted with TC-1 tumor cells after mHTV vaccination, most of the immunized mice were protected from the tumor challenge. In conclusion, mHTV showed considerable potential as not only a therapeutic vaccine, by efficiently killing cancer cells, but also as a prophylactic vaccine by enhancing T cell-mediated immune responses.